2013
DOI: 10.3758/s13414-013-0428-y
|View full text |Cite
|
Sign up to set email alerts
|

Guidance of attention by information held in working memory

Abstract: Information held in working memory (WM) can guide attention during visual search. The authors of recent studies have interpreted the effect of holding verbal labels in WM as guidance of visual attention by semantic information. In a series of experiments, we tested how attention is influenced by visual features versus category-level information about complex objects held in WM. Participants either memorized an object’s image or its category. While holding this information in memory, they searched for a target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In particular, Calleja and Rich (2013) found WM-guided capture for distracters that belonged to the same category as an item stored in WM, but only as long as the WM item and the same-category distracter were visually similar. We posit that whether capture extends to semantic associates depends on the specificity of the attentional set that is encouraged by task demands.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In particular, Calleja and Rich (2013) found WM-guided capture for distracters that belonged to the same category as an item stored in WM, but only as long as the WM item and the same-category distracter were visually similar. We posit that whether capture extends to semantic associates depends on the specificity of the attentional set that is encouraged by task demands.…”
Section: Discussionmentioning
confidence: 97%
“…We posit that whether capture extends to semantic associates depends on the specificity of the attentional set that is encouraged by task demands. In Calleja and Rich (2013), for instance, the WM item was always the image of a specific object. Even though participants performed a match-to-category task, the presentation of a specific image as the WM item may have interfered with the implementation of an abstract attentional set.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For neutral items, engagement of attention in certain items presented in a search array has been shown to be modulated by both bottom-up factors, such as color or motion, and top-down factors manipulated via working memory or priming prior to the search (Wolfe et al, 2003; Burra and Kerzel, 2013; Calleja and Rich, 2013; Woodman et al, 2013). A potential origin of biases in attention to threatening material could be biological preparedness (e.g., Öhman et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…matching stimuli in the visual field, even when there is no explicit intention for observers to voluntarily shift attention to those stimuli (e.g., Calleja & Rich, 2013;Carlisle & Woodman, 2011;Downing, 2000;Han, 2015a;Huang & Pashler, 2007;Olivers, Meijer, & Theeuwes, 2006;Pan, 2010;Soto, Heinke, Humphreys, & Blanco, 2005;. This memory-driven attentional capture cannot be attributable to the mechanism of bottom-up priming by stimulus repetition, as mere priming is usually not sufficient to guide attentional deployment (e.g., Olivers et al, 2006;Pan & Soto, 2010;Soto et al, 2005) and distinct neural mechanisms have been found for attentional biases by working memory and repetition priming (Soto, Humphreys, & Rotshtein, 2007;Soto, Llewelyn, & Silvanto, 2012).…”
mentioning
confidence: 99%